Las nuevas tecnologías de la información y la comunicación (ntic) para el aprendizaje de los presupuestos empresariales en los estudiantes de la universidad Técnica de Cotopaxi, de la carrera de ingeniería comercial en el periodo 2014 - Villarroel Lema, Juan Carlos (2016)
The present research work was born with the need to use the new technologies of information and communication (NTIC) in the educative processes of the subjects of the Commercial Career Engineering from Technical University of Cotopaxi, in this case, focusing on the Enterprise Budget professorship business Budget, this with the objective on improving enterprise skills as an integrated and coordinated plan which express in financial terms with connection to operations and resources that are part of an enterprise for a certain period, in order to achieve the aims set by senior management, combining traditional methodology which the actual environment calls for the research development is used the inductive and deductive method. Also, technique as the survey and a previous statistical analysis, which deduced that is necessary the software application created in Microsoft Office Excel spreadsheets to the budgets professorship; with a practical guide….